Innovative Soaking and Grinding Methods and Cooking Affect the Retention of Isoflavones, Antioxidant and Antiproliferative Properties in Soymilk Prepared from Black Soybean. Issue 4 (8th March 2016) - Tan, Yingying; Chang, Sam K. C.; Zhang, Yan
Abstract: This study's objective was to characterize the effect of traditional and 3 newly devised (soaking+grinding) methods combined with cooking on the content and composition of phenolic substances, antioxidant, and antiproliferative properties of soymilk prepared from black soybean. Phenolic substances and antioxidant profile were characterized and antiproliferation of prostate cancer DU145 cells was conducted using a cell culture assay. Results indicated Grinding Method 4 produced significantly ( P < 0.05) higher total phenolic content (TPC), total flavonoid content (TFC), condensed tannin content (CTC), and total isoflavone content in both raw and cooked black soymilk as compared to Method 1. Cooking soymilk reduced 23% to 38% of total phenolic substances. Raw black soymilk produced by Method 4 displayed the highest antioxidant capability, which was determined using ORAC, FRAP, and DPPH assays, and a higher antiprostate cell proliferation ability. Cooking only slightly reduced the potency to inhibit DU145 prostate cancer cells as IC50 value was increased from the average of about 4.0 mg/mL of raw soymilk extracts to 5.5 mg/mL of cooked soymilk extracts of all grinding methods. Overall, total isoflavone content was the only component that was negatively correlated with IC50 value ( r = –0.93, P < 0.05) which indicates the ability to inhibit prostate cancer cell is associated with the increase in total isoflavone content, not with any other phenolic substances or antioxidant properties.